Role of Ship Guidance in Reducing Accident Risks in Tanjung Perak’s Mandatory Waters - Pantjadjatmika, Pantjadjatmika; Harmuzan, Harmuzan; Mardiana, Mardiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study investigates the effectiveness of ship guidance in minimizing accident risks within the mandatory guidance waters of Tanjung Perak Surabaya. Employing qualitative research methods and descriptive analysis, the research evaluates ship pilot performance based on communication effectiveness, maneuvering precision, regulatory knowledge, emergency response, and professionalism. The findings reveal that effective pilotage significantly enhances navigational safety, contributing to a 20% reduction in accident rates. Despite generally high performance, challenges such as communication barriers, navigational complexity, and regulatory constraints persist. Recommendations include investing in advanced navigational technologies, improving communication protocols, updating regulations for better operational flexibility, and ensuring regular equipment maintenance. The study highlights the critical role of ship pilots in ensuring safe maritime operations and provides actionable insights for optimizing pilotage practices to further enhance safety in complex navigation environments